Postcolonial theory as a hermeneutical tool for Biblical reading - Rukundwa, Lazare S. (HTS teologiese studies, 2008)
In this article, postcolonial theory is presented as a tool for Biblical interpretation, in an attempt to find colonial intentions (be they political, cultural or economic) that informed and influenced the writer’s context. Although criticism has been levelled at the church and other religious institutions for having, consciously or unconsciously, facilitated colonial conquests and imperial establishment all over the world, postcolonial theory calls them to a constructive reading that enables readers to see the concerns of the universal mission of justice. Postcolonial theory, as a tool for Biblical interpretation, deals with the Bible as a “cultural product” in time and space. However, as part of socio-scientific method, postcolonial theory encounters some crucial translation problems such as ethnocentrism and anachronism. Nevertheless, whatever hermeneutical tool the reader uses, it must yield two important things from Scripture reading: discovering life and discovering faith.